2019
DOI: 10.1016/j.chroma.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of aqueous phases of bio-oils resulting from pyrolysis of different biomasses by two-dimensional comprehensive liquid chromatography

Abstract: Agrifood by-products are perfect candidates to be further processed under the concept of circular economy, in order to produce their valorization. Although significant amounts of food-related wastes that are discarded are produced worldwide, these might still be rich in valuable compounds. A strategy to further valorize agrifood-related by-products is based on pyrolysis processes. The result of this process is a liquid product termed bio-oil which is composed of an organic phase and an aqueous phase. This bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Finally, calculate the "corrected" peak capacity achieved, considering both orthogonality and undersampling, the maximum limit of 522 peaks for unripe guabiroba and 418 peaks for ripe guabiroba, were attained. Similar values were obtained by Montero et al [25], Arena et al [26], and Lazzari et al [27] employing RP-LC×RP-LC…”
Section: Lc×lc Methods Optimizationsupporting
confidence: 88%
“…Finally, calculate the "corrected" peak capacity achieved, considering both orthogonality and undersampling, the maximum limit of 522 peaks for unripe guabiroba and 418 peaks for ripe guabiroba, were attained. Similar values were obtained by Montero et al [25], Arena et al [26], and Lazzari et al [27] employing RP-LC×RP-LC…”
Section: Lc×lc Methods Optimizationsupporting
confidence: 88%
“…As viable alternative for enhancing the overall separation capability, comprehensive 2D‐LC (LC × LC) has been far employed for phenol determination in many food and natural products as witnessed by several recent research and review articles [21–34]. It was already reported that LC × LC minimize matrix interferences at the detector, because of the higher resolving power, viz .…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds and aldehydes are mainly derived from lignin and cellulose degradation, respectively [39]. Benzenediols, derived from lignin degradation, remain mainly in the aqueous phase while other phenols, such as alkyl and methoxyphenols, are commonly found in higher concentration in the bio‐oils [18,40]. 5‐(Hydroxymethyl) furfural, 5‐methylfurfural, and furfural are the main compounds formed from cellulose thermal degradation [39] and were identified in all aqueous samples, though with different concentrations levels.…”
Section: Resultsmentioning
confidence: 99%
“…Method performance was evaluated through the assessment of the main figures of merit: dynamic range, linearity, limits of detection and quantification, precision (intra‐ and interday) and accuracy (by recovery). All the validation procedure was according ANVISA [31] protocols as previously reported in detail [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation